SISTEM PENGEMBALIAN PEMBIAYAAN MUDHARABAH (Studi pada Koperasi Jasa Syariah Barokah Curup) - Muhammad Istan; Idi Warsah (Universitas Islam Negeri Ar-Raniry, 2018)
The main purpose of this research is to know how mudharabah contract implementation in Sharia Cooperative Barokah Curup and how the implementation of profit sharing system at mudharabah financing in Sharia Cooperative Barokah Curup. This research used a desciptive qualitative approach. The main data source of this research derived from field data by collecting data from informants in this case is the Cooperative Services Sharia Barokah Curup. In addition, the data also obtained from literature study and documentation. The results show that the most important thing in mudharabah financing is the honesty of both parties, especially the fund manager. Because the profit is divided is the result of effort (reveneu sharing) and profit sharing (profit sharing). Financial data information is derived from financial statements by fund managers. 1) Mudharabah agreement implemented in Sharia Barokah Cooperative is divided into two, namely pure mudharabah and mixed mudharabah. 2) The model of return on the financing of pure mudaraba is divided into two, namely the system of repayment principal of mudharabah financing by installment and financing repayment model by way of total repayment. As for the model of return on the financing of mixed mudharabah use mudharabah refinancing only model by installment.